Effects of physical, non-immersive virtual, and immersive virtual store environments on consumers' perceptions and purchase behavior - Lombart, Cindy; Millan, Elena; Normand, Jean-Marie; Verhulst, Adrien; Labbé-Pinlon, Blandine; Moreau, Guillaume (Computers in human behavior, 2020)
The application of virtual reality in human activities has been rapidly growing during the last decade. Shopping for food is an important part of people's daily lives. As overnight delivery services of fresh produce, such as Amazon Fresh, are in their development stage, more studies on virtual stores for perishable products are needed, as the quality of fruits and vegetables (FaVs) cannot be easily assessed by consumers when virtual stores are used. This research examines the impact of a physical store, a non-immersive virtual store, and an immersive virtual store environment on consumers' perceptions and purchase behavior toward FaVs. Experimental between-subjects design (i.e., three groups), combined with a questionnaire survey (after-only design), was used to address the study objectives. The research found that consumers' perceptions of FaVs in both non-immersive and immersive virtual stores (VS) are similar to those in a physical store. By contrast, consumers buy more FaVs in both non-immersive and immersive VS compared to a physical store. The findings also indicate that consumers tend to rely more on extrinsic cues (i.e., FaVs' prices) in the immersive VS when evaluating FaVs on offer and less on intrinsic cues (e.g., FaVs' appearance) they use in the physical store. The results have important implications for practitioners and researchers with regard to the usefulness of virtual reality for better understanding of consumer behavior. •Consumers' perceptions of FaVs in both non-immersive and immersive VS are similar to those in a physical store.•Consumers buy more FaVs in both non-immersive and immersive VS compared to a physical store.•Consumers tend to rely more on extrinsic cues (i.e., FaVs' prices) in the immersive VS.•Consumers tend to rely more on intrinsic cues (e.g., FaVs' appearance) in the physical store.